2016
DOI: 10.1007/s10666-016-9502-x
|View full text |Cite
|
Sign up to set email alerts
|

Contact Tank Design Impact on Process Performance

Abstract: In this study three-dimensional numerical models were refined to predict reactive processes in disinfection contact tanks (CTs). The methodology departs from the traditional performance assessment of contact tanks via hydraulic efficiency indicators, as it simulates directly transport and decay of the disinfectant, inactivation of pathogens and accumulation of by-products. The method is applied to study the effects of inlet and compartment design on contact tank performance, with special emphasis on turbulent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…This suggested that the best value for the Sc t could be related to the characteristics of the flow field in a contact tank [53]. More recently, Angeloudis et al [26][27][28][29] used Sc t = 0.7 to study the effect of tank geometry on the disinfection efficiency confirming the key role of this parameter in the reliable prediction of the tracer transport in a contact tank. The same value was adopted by Martínez-Solano et al [54] to study flow and concentration fields in a rectangular water tank [32].…”
Section: Water Systemsmentioning
confidence: 96%
See 2 more Smart Citations
“…This suggested that the best value for the Sc t could be related to the characteristics of the flow field in a contact tank [53]. More recently, Angeloudis et al [26][27][28][29] used Sc t = 0.7 to study the effect of tank geometry on the disinfection efficiency confirming the key role of this parameter in the reliable prediction of the tracer transport in a contact tank. The same value was adopted by Martínez-Solano et al [54] to study flow and concentration fields in a rectangular water tank [32].…”
Section: Water Systemsmentioning
confidence: 96%
“…A number of studies about the turbulent Schmidt number have dealt with the simulation of flow and tracer transport in open channels [22][23][24][25], while others have addressed those issues in contact or water tanks [26][27][28][29][30][31][32][33][34][35][36], inclined negatively-buoyant discharges [37], sediment-laden open channel flows [38][39][40][41][42][43][44][45][46][47][48], density stratified turbulence [49,50] and T-junction mixing experiments [51] ( Table 2). The terms "Exp" and "Num" mean the application of experimental and numerical methods, respectively, in each study.…”
Section: Water Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional numerical simulations were conducted by Zachary et al [2] in order to maximize the disinfection efficiency of the contactor by modifying the hydraulic design of baffles. Guiding walls were included in the contact tank in order to minimize the recirculation effects [3]. The relationship between the baffling performance and energy loss for the definition of "hydraulic efficiency" of the contact tank system was investigated by Zhang et al [4], where the authors stated that the energy saving afforded by using more baffles in the contactor was offset by the extra energy necessary to drive the flow through the contact tank system.…”
Section: Introductionmentioning
confidence: 99%
“…were associated with carbohydrate utilization and selected enzymes showed different levels of inhibition by monochloramine when tested (Coburn et al, 2016). Angeloudis et al (2016) refined 3D numerical models to predict reactive processes in disinfection contact tanks with special emphasis on turbulent mixing and minimization of internal recirculation and short-circuiting. The results suggested that water treatment facilities can benefit from in-depth analyses of the flow and kinetic processes through computational fluid dynamics, resulting in up to 38 % more efficient pathogen inactivation and 14 % less disinfection byproducts (DBPs) formation.…”
mentioning
confidence: 99%